Evidence for different drivers behind long‐term decline and depression of density in cyclic voles. Issue 4 (23rd September 2015) - Magnusson, Magnus; Hörnfeldt, Birger; Ecke, Frauke
Abstract: Decline and long‐term depression of mean densities of the grey‐sided vole ( Myodes rufocanus ) and the field vole ( Microtus agrestis ) have occurred in managed forest landscapes of Sweden since the 1970s. Generally poor over‐winter survival during a period with mild winters suggested a common climatic driver, but other explanations exist. Here we explore the response of the grey‐sided vole, preferring forested habitats, and the field vole, preferring open habitats, to clear‐cutting of old forest in Sweden. The cumulated impact from long‐term clear‐cutting explained local disappearances of the grey‐sided vole. Maintained connectivity of old forest to stone fields was important for local population survival, since no such populations disappeared. For the grey‐sided vole, it is probable that climate is not the dominating driver due to different timing of the decline in our study area. Instead, habitat loss is concluded as being a potential cause of the decline in mean density and depression of grey‐sided vole densities. The long‐lasting depression of field vole densities, despite favourable landscape changes, suggests action of another strong driver. A recent field vole recovery, essentially back to pre‐decline densities and distribution, coincided with favourable winter/snow conditions, suggesting a climatic driver in this case.